A Chirp-Managed Tunable DBR Laser Based on Novel Cascaded Gratings - Yao Zhu; Congying Feng; Yuze Wu; Yonglin Yu (IEEE Photonics Journal, 2018)
In this paper, a novel tunable DBR laser based on novel cascaded gratings is proposed for chirp management in high-speed direct modulation applications. The cascaded gratings, i.e., a tilted $π $ phase-shift grating followed by a normal uniform Bragg grating, can provide a narrow-band reflection spectrum with a sharp falling slope on the longer wavelength side, so that the optical spectrum shaping and the detuned-loading effects can be enhanced. Simulation results indicate that the wavelength tuning range of the laser is about 10 nm and the 3-dB modulation bandwidth reaches up to 25 GHz. By simply adjusting the phase current and thus changing the detuned frequency, the extinction ratio and the frequency chirp can be optimized, which is helpful to improve the dispersion tolerance and reduce the dispersion power penalty.